Dune : the graphic novel. Book 1 - Herbert, Brian (Abrams Comicarts, 2020)
"Dune, Frank Herbert's epic science-fiction masterpiece set in the far future amidst a sprawling feudal interstellar society, tells the story of Paul Atreides as he and his family accept control of the desert planet Arrakis. A stunning blend of adventure and mysticism, environmentalism, and politics, Dune is a powerful, fantastical tale that takes an unprecedented look into our universe, and is transformed by the graphic novel format. In the first volume of a three-book trilogy encompassing the original novel, Brian Herbert and Kevin J. Anderson's adaptation retains the story's integrity, and Raúl Allén and Patricia Martín's magnificent illustrations, along with cover art by Bill Sienkiewicz, bring the book to life for a new generation of readers." --